Goals-of-care and serious illness conversations for patients with cancer with inpatient mortality. Issue 28 (1st October 2022) - Lee, Julie Jiyun; Wheless, Margaret; Domenico, Henry; Martin, Barbara; Bennett, Marc; Green, Jennifer Kiser; Agarwal, Rajiv
Abstract : 184 Background: Goals-of-care (GOC) and serious illness conversations are an integral part of personalized cancer care, particularly toward the end of life (EOL). Eliciting patients (pts)' preferences and values facilitates informed decision-making throughout the disease course and enables oncologists to provide patient-centered care. Many aspects of GOC discussions and advance care planning (ACP) are inadequately understood, particularly during transitions of care when pts are hospitalized. Methods: We administered surveys to inpatient and outpatient medical oncologists of pts who died while hospitalized from 5/1/2020 to 5/31/2021. Survey items included oncologists' knowledge of inpatient death, anticipation of pt death within six months of admission, recollection of GOC discussions taking place, and perceived barriers to GOC discussions. To better characterize EOL planning for these pts, retrospective data was collected to identify documentation of GOC discussions, advance directives, and hospice consideration in pts' electronic health records. Results: For 75 cancer pts who died while hospitalized, 158 surveys were electronically administered with 104 responses (response rate: 66%). Pts characteristics: median age 62 (range 25-89); 63% men; 79% white; median length of hospital stay 7 days (range 1-45). Primary cancer disease type varied: 26.7% gastrointestinal, 18.7% non-small cell lung, 14.7% hematologic, 10.7% sarcoma, 9.3% genitourinary, and 19.9% other cancers. Of 104 completed surveys, responses were received from 40 inpatient and 64 outpatient oncologists. 81 oncologists (77.9%) were aware of the pt's death prior to survey communication, 68 (65.4%) anticipated the pt's death within six months of admission, and 67 (64.4%) recalled having a GOC discussion prior to or during the terminal hospitalization. Only 21.3% of pts had documented GOC discussions prior to admission, 33.3% had advance directives, and 22.7% had prior documentation of hospice consideration. Oncologist-reported barriers to GOC discussions included unrealistic expectations from pts or family (25%) and inability for pts to participate due to their clinical condition (15%). Oncologists commented on lack of time, lack of communication between inpatient and outpatient teams, and discordance among multiple inpatient providers as additional barriers. Conclusions: Most oncologists recalled having GOC discussions and anticipated six-month mortality for cancer pts who died while hospitalized. However, documentation of ACP and serious illness communication remained sub-optimal. Ongoing analyses are examining potential associations between patient, provider, and patient-provider relationship factors and oncologists' survey responses. Addressing barriers to serious illness conversations across different healthcare settings is crucial to providing high-quality EOL care for cancer pts.